The formation and organization management of the "One Syndrome and One Product" construction work program ("一证一品"建设工作方案的形成与组织管理) - JI Yingxia (季英霞); CAO Yanxia (曹艳霞); WANG Jingyun (王静云); CHEN Yixiu (陈一秀); GAO Xinxia (高新霞); XU Huirong (许慧荣); WANG Donglan (王东兰) (Association of Integrative Nursing, 2021)
This paper summarized the formation and organization management of the "One Syndrome and One Product" construction work program in a Traditional Chinese Medicine hospital. The goal, work requirement, training and evaluation plan of the ward construction of TCM nursing specialty model of "One Syndrome and One Product " were clearly defined in the work plan, and suggestions were provided for further construction and development of "One Syndrome and One Product " demonstration wards. (本文主要总结"一证一品"建设工作方案的形成与项目的组织管理, 包括"一证一品"中医护理专科模式病房建设的目标、工作要求、培训与评价方案等, 以期为进一步规范、科学开展"一证一品"示范病房建设项目提供参考。)